ISLAMIC ESCHATOLOGICAL TERMINOLOGY: UNDERSTANDING THE LANGUAGE OF THE END TIMES - Khairun Nabilah binti Khairuddin; Mohd Yusuf Ismail (International Prophetic Conference (SWAN) FPQS USIM, 2024)
This article explores the key terminologies associated with Islamic eschatology, focusing on the language used in Quranic verses and prophetic traditions that describe the events of the End Times. By analyzing the semantic structure and theological implications of these terms, the study aims to provide a clearer understanding of how Islamic texts communicate concepts related to eschatological beliefs. The research identifies and categorizes the primary words and phrases used in classical Islamic sources to describe major eschatological events, such as the emergence of the Dajjal, the descent of Isa (Jesus), and the occurrence of the Hour (al-Sa'ah). Through a critical examination of these terms, the article highlights the significance of specific language choices in shaping Muslim perceptions of the apocalyptic future. The study also addresses the challenges of interpreting these terms in both their historical and contemporary contexts, offering insights into the evolving understanding of Islamic eschatology. This analysis contributes to the broader field of Islamic studies by clarifying the linguistic foundations that underpin eschatological discourse.